Metals in proteins from sulphate-reducing bacteria: adenylate kinase and ATP sulfurylase. Proteins containing cobalt, zinc, iron (II) ions - Kladova, Anna Vadymivna (2011)
A Thesis submitted at the Faculty Science and Technology of the New University of Lisbon for a degree in Doctor of Philosophy in Biochemistry with specialization in Physical Biochemistry